2022
DOI: 10.1186/s40779-022-00426-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of the immune microenvironment in bone, cartilage, and soft tissue regeneration: from mechanism to therapeutic opportunity

Abstract: Bone, cartilage, and soft tissue regeneration is a complex spatiotemporal process recruiting a variety of cell types, whose activity and interplay must be precisely mediated for effective healing post-injury. Although extensive strides have been made in the understanding of the immune microenvironment processes governing bone, cartilage, and soft tissue regeneration, effective clinical translation of these mechanisms remains a challenge. Regulation of the immune microenvironment is increasingly becoming a favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 298 publications
1
90
0
Order By: Relevance
“…These pro-inflammatory cytokines augment the activity of osteoclasts and decrease the recruitment or migration of MSCs. This results in bone disconnection and poor osseointegration [ 68 72 ]. In this study, Ti-PDA@SNP-OGP significantly down-regulated the mRNA expression levels of M1 markers CD86, iNOS, and CD11C and up-regulated the mRNA expression levels of M2 markers CD206, Arg-1, and CD163.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pro-inflammatory cytokines augment the activity of osteoclasts and decrease the recruitment or migration of MSCs. This results in bone disconnection and poor osseointegration [ 68 72 ]. In this study, Ti-PDA@SNP-OGP significantly down-regulated the mRNA expression levels of M1 markers CD86, iNOS, and CD11C and up-regulated the mRNA expression levels of M2 markers CD206, Arg-1, and CD163.…”
Section: Discussionmentioning
confidence: 99%
“…The crosstalk between MSCs and RAW264.7 cells plays a vital role in the improvement of implant osseointegration [ 72 74 ]. Therefore, the osteogenic induction effect of RAW264.7 cells on MSCs upon the stimulation of Ti-PDA@SNP-OGP should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…There are four continuous and overlapping stages involving with the regeneration of both the bone and the cartilage tissues, including hemostasis, inflammation, repair, and remodeling ( Fig. 7 A) [ 324 ]. Tissue engineering strategies with the use of MZSs for OC regeneration mainly play direct roles in the latter two stages.…”
Section: Cell Sources and Growth Factors In Mzssmentioning
confidence: 99%
“…Adapted with permission from Ref. [ 324 ]. B. Anatomical illustration of major types of cells residing in osteochondral tissue.…”
Section: Cell Sources and Growth Factors In Mzssmentioning
confidence: 99%
“…Since then, researchers have discovered that immune cells not only eliminate microbial and cellular debris but also promote tissue growth and wound repair (12,13). Furthermore, increasing research has revealed the crucial role of immune cells in healing as well as the underlying regulatory mechanism (14,15). In other clinical studies, immunocompromised individuals have been reported to exhibit impaired wound repair, which also indicates the important role of immune cells in skin healing (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%